Shell instability analysis by using mixed interpolation - Rezaiee-Pajand, M.; Masoodi, Amir R. (Journal of the Brazilian Society of Mechanical Sciences and Engineering, 2019)
In this paper, buckling and post-buckling behavior of plates and shells are investigated. An efficient triangular shell element having six nodes is employed in this study. To consider large deflection and rotation, total Lagrangian formulation is utilized. The authors employ mixed interpolation for strain fields to deviate shear and membrane locking phenomena. The effects of different types of boundary conditions and geometry properties of plates and shells are studied. An almost complete literature review is also provided to show the progress of researches about the current topics. Various states of buckling including bifurcation and snap-through are assessed in different problems. In this study, the popular benchmarks of shell structures are analyzed to show the accuracy and capability of element. In addition, some new benchmarks which can be used by other researchers are also introduced and solved. Further, a comparison study between the proposed element and NLDKGQ element in OpenSees software is implemented for some complex curved shell structures.